Experimental Evaluation of Glulam Made from Portuguese Eucalyptus - Aiuba Suleimana; Bárbara C. Peixoto; Jorge M. Branco; Aires Camões (Applied Sciences, 2023)
Engineered wood products (EWPs) have evolved over time to become a popular and sustainable alternative to traditional lumber by offering design flexibility, increased strength, and improved quality control. This work analyzes the potential of Portuguese eucalyptus wood (Eucalyptus globulus) to produce glued-laminated timber (glulam) for structural applications. Currently, this hardwood is used for less noble applications in Portugal’s construction industry. To promote the use of this species of timber in construction, an experimental campaign was conducted to characterize its compression parallel to the grain and bending strength. The results demonstrated that this hardwood presents a compression parallel to the grain strength of 73 N/mm2 and a bending strength of 151 N/mm2 with a global value of elastic modulus equal to 24,180 N/mm2. Based on those strength values obtained from the glulam produced with eucalyptus, one can conclude that the test results presented here are higher than the ones declared by the current glulam made of softwoods; thus, additional studies are encouraged.